Comparative quality assessment in immunocytochemistry: pilot study of CD15 staining in paraffin wax embedded tissue in Hodgkin's disease. Issue 10 (October 1989) - Angel, C A; Warford, A; Day, S J; Lauder, I
Abstract : The feasibility of comparative quality assessment studies in immunocytochemistry was examined. The reactions of three CD15 antibodies--anti-Leu M1, DM1, and Tü9--were examined in paraffin wax sections in Hodgkin's disease under a variety of different fixation and pre-treatment conditions, using four immunochemical detection techniques. All three antibodies stained Reed-Sternberg cells, but DM1 could be used at slightly higher dilutions to achieve comparable results. Tissue fixed in formol sublimate showed the most intense staining reactions, and formol saline and neutral buffered formalin gave relatively poor results. Although neuraminidase pre-treatment improved staining, its routine use is probably contraindicated by its high cost. Trypsinisation has some value for sections of tissue fixed in formol saline and neutral buffered formalin. The avidin-biotin complex technique produced the best results, but indirect immunoperoxidase produced acceptable results, is technically easier to perform, and is less expensive. It is concluded that information regarding variations in techniques and commercially available reagents, which may be of use in routine diagnostic histopathology, can be obtained by comparative quality assessment studies of this type.